Distribuição de anticorpos neutralizantes contra o Herpevírus bovino 1 (HVB1) em rebanhos bovinos de aptidão leiteira e de corte do estado de Minas Gerais - Cristiano Barros de Melo (1998)
The dinamic of distribution of neutralizing antibodies for the bovine herpesvirus l (BHV 1) ir1 four different age 24 beef and dairy cattle · herds was studied. The serology was correlated with the answers of a form, applied on the farms analised. The prevalence rates of neutralizing antibodies for the BHV 1 was determined and compared among the types of exploration and age animals. Problems like the type of manegement used on the herds and the age of the animals were implied in the distribuition of neutralizing antibodies against this virus in the herd.